The school historiography of Franco´ s baccalaureate from the perspective of the issuer - Castillejo Cambra, Emilio (Clio. History and History Teaching, 2022)
This article establishes the relationship between the message of some History textbooks of Franco's Baccalaureate (29 in total) and the political position of their authors, whether they were punished (purged from the educational category of professors in 1935) or rewarded with patriotic examinations in 1940 which favored those who were accomplices of the 1936 coup d'état. To discover those personal careers, it is necessary to use secondary historical sources. While some authors use the History textbook to confirm their loyalty to Franco's regime, others use it as safe-conduct to separate themselves from their past, whether it was masonic, left republican, or catalanist. Some authors, such as José Ramón Castro, are coherent with his professional and school historiographical works (their fidelity to the regime is unwavering). Others, such as Jaime Vicens Vices or Antonio Domínguez Ortiz, represent the official culture (they legitimize the regime) as school textbook writers; but as professional historians, they do represent the so-called established culture, that distances itself from the regime and its values.
Keywords: Key words: Francoism. Depuration of professors. Patriotic examinations. Manual of History. Manual - safe conduct.; Francoism; Depuration of professors; Patriotic examinations; Manual of history; Manual - safe conduct